The ancient formula : a mystery with fractions - Thielbar, Melinda (Thielbar, Melinda. Manga math mysteries, 2011)
The students of Sifu Faiza's Kung Fu School use their knowledge of fractions as they try to discover what happened to Leung Jan's long-lost healing formula.